2019
DOI: 10.2174/0929866526666190620145919
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Molecular Simulation in the Discovery of Antituberculosis Drugs: A Review

Abstract: : After decades of efforts, tuberculosis has been well controlled in most places. The existing drugs are no longer sufficient for the treatment of drug-resistant Mycobacterium tuberculosis due to significant toxicity and selective pressure, especially for XDR-TB. In order to accelerate the development of high-efficiency, low-toxic antituberculosis drugs, it is particularly important to use Computer Aided Drug Design (CADD) for rational drug design. Here, we systematically reviewed the specific role of molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…Molecular dynamics (MD) simulation, based on Newtonian mechanics, is one of the important techniques used to study the thermodynamic and kinetic properties of biomolecules. 43,44 In this work, three independent MD simulations at 300 K were performed for the SHP2 systems with the AMBER20 package, 45 where OL15 and ff14SB force field parameters were respectively adopted for the nucleic acid and protein atoms. 46 It should be noted that the SHP2 (SH2 structural domain only) system studied was based on the crystal structure (PDB ID: 2SHP) with all solutes dissolved in the octahedral box with the boundary of 15.0 Å using the TIP3P water model.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation, based on Newtonian mechanics, is one of the important techniques used to study the thermodynamic and kinetic properties of biomolecules. 43,44 In this work, three independent MD simulations at 300 K were performed for the SHP2 systems with the AMBER20 package, 45 where OL15 and ff14SB force field parameters were respectively adopted for the nucleic acid and protein atoms. 46 It should be noted that the SHP2 (SH2 structural domain only) system studied was based on the crystal structure (PDB ID: 2SHP) with all solutes dissolved in the octahedral box with the boundary of 15.0 Å using the TIP3P water model.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Other than the corrosion field, MD simulation also offers numerous advantages in various sectors such as renewable energy generation, food technology, medicine, and pharmaceutical [15][16][17][18]. A broad list of reviews of MD simulation application for corrosion sector as well as other sectors had been published in the literature [14,[19][20][21][22]. In this context, numerous works have shown that MD simulation is a promising method to obtain the molecular level information of a system.…”
Section: Introductionmentioning
confidence: 99%